The Effect of Quality of Work Life on Generation Y Employee Engagement Through Job Satisfaction as a Mediator Variable at PT.C - Novitasari, Aulia (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
—Employee Engagement is one aspect of the company's success to achieve the company's goals optimally. This study aims to analyze the effect of Quality of Work Life on Employee Engagement of Generation Y employees with Job Satisfaction as a mediator variable at PT.C. This study uses the Structural Equation Model – Partial Least Square (SEM-PLS) method. This research was conducted at PT.C with a sample of seventy-seven respondents. The results of this study indicate that Quality of Work- Life has a positive and significant effect on employee Engagement, Quality of Work Life has a positive and significant effect on Job Satisfaction, Job Satisfaction has a positive and significant effect on Employee Engagement, there is an indirect effect between Quality of Work Life on Employees Engagement through job satisfaction positively and significantly.